Does Confucian culture reduce corporate default risk? Evidence from China - Wu, Sha; Wan, Mengfei (Applied economics, 2024)
Confucianism is the cornerstone of traditional Chinese culture, and it has a significant impact on corporate behaviour. This paper investigates the relationship between Confucian culture and default risk. Using a sample of Chinese listed companies that covers the period between 2010 and 2020, we find robust evidence that Confucian culture is negatively associated with the probability of default. The effect operates through improvements in reputation and resource acquisition. It is more pronounced at firms that face severe financing constraints, at firms that are located in regions with high marketization, and at firms that are subject to weaker external supervision. Additional analyses show that Confucian culture improves corporate social responsibility and the quality of internal control, reduces earnings management and corporate risk-taking, and, ultimately, decreases the overall value of the firm. On the whole, our findings provide evidence of the role of cultural factors in filling institutional voids.